P555 Monitoring HIV and syphilis co-infection among men who have sex with men in brazil, 2009–2016. (14th July 2019) - Guimaraes, Mark; Veras, Maria; Dourado, Inês; Macena, Raimunda; Brito, Ana; Rocha, Gustavo; Motta-Castro, Ana Rita; Kerr, Ligia
Abstract : Background: HIV and Syphilis, including co-infection, are increasing among men who have sex with men (MSM) in several countries. The objective of this analysis is to compare the prevalence of HIV-syphilis co-infection, HIV only, or syphilis only among MSM in Brazil in 2009 and 2016 and and associated factors for 2016. Methods: Two MSM Respondent Driven Sampling (RDS) cross-sectional studies were carried out in 2009 (10 cities) and 2016 (12 cities) in Brazil. HIV and syphilis serology were performed using standard rapid tests.Risk behavior and sociodemographic data were obtained. RDS weighted prevalence rates with 95% confidence intervals (95%CI) were estimated. Poisson regression was used to estimate the prevalence rate ratio (PRR) and 95%CI of each outcome, as compared to those with no infection. Results: The prevalence rates of syphilis only (80% increase) and HIV-syphilis co-infection (136% increase) were significantly different between 2009 and 2016 (Table 1). HIV only was relatively stable. For 2016 data, older age (25+ y.o.) and previous diagnosis of sexually transmitted infections were independently associated with co-infection, PRR=2.49 (95%CI=1.87–3.31) and 5.50 (95%CI=4.31–7.02), respectively. Other predictors were heterogenous with regard to different outcomes. Conclusion: Although the prevalence rate of HIV infection alone did not increase so between 2009 and 2016, it is of extreme concern the increase in rates of syphilis, alone or as co-infection with HIV, among MSM in Brazil. Treatment and prevention efforts may not be reaching those at higher risk and may lack effectiveness. Syphilis may be an important drive of the persistence of the HIV epidemic among MSM in Brazil. Nationwide public health actions, including syphilis testing, treatment and reiterating consistent condom use, are urgently needed. Disclosure: No significant relationships.